Blood Pressure and Late Pregnancy Circulating miRNAs in the MADRES Study - Elizabeth C. Anderson; Meghan E. Muse; Zhongzheng Niu; Helen B. Foley; Joshua J. Levy; Megan E. Romano; Jiang Gui; Jessica L. Bentz; Shohreh F. Farzan; Theresa M. Bastain; Carmen J. Marsit; Carrie V. Breton; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Circulating extracellular and vesicle particle (EVP) miRNAs have been associated with cardiovascular risk and adverse birth outcomes. Hypertensive disorders of pregnancy (HDP) increase risk for adverse birth outcomes and future cardiovascular outcomes in mothers and children and have been associated with altered maternal circulating EVP miRNA levels during pregnancy. Whether these relationships exist for elevated blood pressure (BP) in the subclinical range is unknown. We investigated associations between (1) hypertensive disorders of pregnancy and (2) maternal BP trajectories, including in the subclinical range, and circulating EVP miRNA levels during pregnancy in the MADRES (Maternal and Developmental Risks From Environmental and Social Stressors) Study (n=372). Methods Latent class trajectory modeling was used to identify trajectories from BP measures abstracted from medical records. The NanoString nCounter platform was used to quantify 798 miRNAs extracted from maternal blood (median gestational age: 31.6 weeks). Covariate‐adjusted regression models assessed associations between each hypertensive disorders of pregnancy subtype or BP trajectory and levels of each miRNA. Results Three BP trajectories were identified: Low, Moderate, and High. Chronic hypertension was associated with higher levels of miR‐1185‐2‐3p (Pfalse discovery rate<0.05), a placenta‐specific miRNA linked to arterial stiffness and preterm delivery. Many placenta‐expressed miRNAs previously associated with a longer gestational duration in the same cohort were lower among participants with elevated BP (P<0.05). Target genes of BP‐associated EVP miRNAs were overrepresented in pathways involved in vascular inflammation, oxidative stress, endothelial dysfunction, and placental function. Conclusions Circulating levels of placenta‐expressed EVP miRNAs previously implicated in adverse birth and cardiovascular outcomes are sensitive to elevated maternal BP during pregnancy, including in the subclinical range.